ASPECTS OF SECOND LANGUAGE TEACHING TO INDIGENOUS PEOPLES OF CANADA: The Challenges for Indigenous Religious Freedom in Canada Today (Canadian Journal of Native Studies, 2026)
AbstractThe aim of this article is to provide second language teachers and coursedesigners working with Indigenous learners with elements of theoriesand practices that best suit their learners needs. In order to do that, tworeviews of literature are presented: the first one deals with Eurocentricsecond language didactics paradigm in use today and the second onedeals with traditional Indigenous education principles and techniques.A conceptual frame of second language teaching to Indigenous learnersis then provided and practical suggestions are given to teachers andcourse designers working with this clientele.